191k views
3 votes
Solve the equation 3(x+1)=5-2(3x+4)

1 Answer

1 vote

3(x+1)=5-2(3x+4)

To solve the given equation:

1. Remove parenthesis:

Use distributive property:


a(b+c)=ab+ac
3x+3=5-6x-8

2. Combine like terms:


3x+3=-6x-3

3. Substract 3 in both sides of the equation:


\begin{gathered} 3x-3+3=-6x-3+3 \\ \\ 3x=-6x \end{gathered}

4. Add 6x in both sides of the equation:


\begin{gathered} 3x+6x=-6x+6x \\ 9x=0 \end{gathered}

5. Divide into 9 both sides of the equation: (0 divided into any number is equal to 0)


\begin{gathered} (9)/(9)x=(0)/(9) \\ \\ x=0 \end{gathered}

6. Prove the x=0 in the original equation:


\begin{gathered} 3(0-1)=5-2(3(0)+4) \\ 3(-1)=5-2(4) \\ -3=5-8 \\ -3=-3 \end{gathered}

As x=0 make a true the equation (-3 is equal to -3). The solution is correct

The solution for the equation is x=0
User Engie
by
4.8k points